PSYCHOMETRIC TESTS APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Iwan Setiawan Rahman; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2005)
Although a very large capacity of the human brain, we only use an average of two per cent of our potential brain power, we therefore have the potential to expand our brainpower and testing (testing) on a regular basis as a key method that brain power. Psychometric tests covering subjects such as personality tests that include lateralitas tests, creativity tests are based on patterns of thoughts, feelings, behaviors and knowledge, and measure the range of human aspects. An intelligence test tests used untukmengukur level thinking skills a person. One of the problems that arise in every human being has a personality that has different capabilities, including lateralitas, creativity and intelligence. In this case the characteristics that distinguish ourselves with others. Based on these problems the writer tries to pick and find a solution by giving a practical illustration through the questions will be answered in psychometric tests. In writing this scientifically demonstrated several ways to solve the problem, including using application analysis, program design, menu structure, program flowchart, design and configuration of input and output of the computer and the discussion of issues.